Dua Budaya, Pertanian dan Industri - Mata pencaharian dalam Masyarakat Pesisir Dukuh Tapak, Tugurejo, Tugu, Kota Semarang - Ningwuri, Astrid Aditika (Sabda: Jurnal Kajian Kebudayaan, 2015)
This study examines two cultural forms of livelihood in coastal communities Dukuh Tapak, Kelurahan Tugurejo, Semarang. This research purpose is to identify the conditions of each individual and family livelihood, a reason to the dualism of livelihood, and the influence of industry on the social and economic life. This research use a qualitative method, collecting primary data through in-depth interviews and observation, secondary data obtained from study of literature and documents. The results showed that Dukuh Tapak's people have a livelihood as factory employees while managing the fish farm as a sideline. Most people who work in factories are women and youth as a bid to shore up their family economy. Industrialization did not significantly affect the socio-economic conditions, in which a sense of kinship and mutual help are still well preserved. While in terms of economic, a family with two types of livelihood tend to be more established than a family with only working either in the industry or the agricultural sector.